Risk Management, Disaster Mitigation in the University Environment - Saputro, Diyon; Nasrulloh, Rifqi Syarif (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
Natural disasters present conditions that can lead to significant damage and pose a threat to the survival of society. Addressing and mitigating the risks associated with these disasters is imperative. One approach involves the implementation of risk management and disaster mitigation strategies. Despite the widespread acknowledgment of these measures, their application in the tertiary sector remains limited. This study focuses on Nadhlatul Ulama University in Yogyakarta, aligning with the emphasis on disaster mitigation at the university level as outlined in Minister of Education and Culture Regulation Number 33 of 2019, which pertains to the Implementation of Disaster-Safe Education Units. Utilizing a qualitative research design with descriptive methods, data collection involves structured interviews. Purposive sampling is employed to select informants capable of providing insights relevant to the study's focus. The research yields an initial model for a disaster-safe university, aiming to enhance understanding of school-based disaster risk reduction models and programs within communities vulnerable to potential disasters. The disaster risk reduction program is encapsulated in an initiative named